Religion and Health Among Older Mexican Americans: Exploring the Influence of Making Mandas - Krause, Neal M. (Journal of religion and health, 2012)
A manda is a religious quid pro quo whereby an older Mexican American promises to perform a religious act if the Virgin or one of the saints grants a request. The purpose of this study is to see whether making mandas is associated with health among older Mexican Americans. Findings from the study model suggest that making mandas is associated with a greater sense of personal control, and more personal control is associated, in turn, with better health.